Presenting a model for predicting marital boredom based on differentiation, emotional intelligence and mental health mediated by resilience in couples - Mehdigholi, Mohamadreza; Dokanei fard, Farideh; Jahangir, Pantae (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to evaluate the fit of the prediction model of marital burnout based on differentiation, emotional intelligence and mental health mediated by resilience in couples. Method: The research method was correlational, structural equation modeling type. The statistical population included all couples referring to family counseling centers in District 1 of Tehran in the second half of July to the end of September 2021, in which 248 couples (124 males and 124 females) were selected by non-random sampling method. They were evaluated using the Marital Burnout Scale (Pines, 1996), Emotional Intelligence (Shut et al., 1998), Resilience (Connor & Davidson, 2003), and Differentiation of Self Questionnaire (Skowron and Dandy, 2003) and General Health Questionnaire (Goldberg & Hiller, 1972) were evaluated. Results: obtained from the evaluation of the proposed model by structural equation using SPSS23 and Smart PLS3 software showed that the model fit indices have a desirable level. There is a significant relationship between differentiation (P< 0.05) and mental health (P<0.01) and marital burnout, but there is no significant relationship between emotional intelligence and marital burnout. Resilience also does not mediate the relationship between differentiation, emotional intelligence and mental health and marital burnout. Conclusion: Based on the findings of the present study, it can be said that differentiation and mental health play an important role in marital burnout of couples, so paying attention to these variables will help researchers and therapists in the field of couple and family in prevention and designing appropriate therapies.